Inequalities in disease burden and care quality of neglected tropical diseases and malaria, 1990-2021: Findings from the 2021 Global Burden of Disease Study. - Ran He; Wenhao Zhu; Shirong Hui; Meijie Yu; Haochang Li; Yihao Li; Peng Huang; Rongbin Yu (PLoS ONE)
Background Neglected Tropical Diseases (NTDs) and malaria represent significant public health threats, particularly in regions with low Socio-Demographic Index (SDI) levels. Despite global efforts to enhance prevention and control, disparities still persist. We aimed to assess the quality of care for NTDs and malaria through the quality of care index (QCI) to analyse differences in regions, genders, age groups, and to provide measures to improve the quality of care to reduce the burden of disease. Methods Using data from the Global Burden of Disease Study 2021 (GBD 2021), four secondary indicators were calculated using six primary indicators: incidence, mortality, prevalence, the disability-adjusted life years (DALYs), years of life lost, and years lived with disability to calculate the QCI through principal component analysis, and the gender disparity ratio was the ratio of female QCI to male QCI. Results Globally, the incidence of NTDs and malaria increased, while age-standardized mortality rates (ASMRs) and DALYs declined from 1990 to 2021. In 2021, the QCI was highest in Bahrain, Qatar, and the United Arab Emirates, with scores of 91.9, 91.5, and 91.5, respectively. In contrast, Uganda, Niger, and Burkina Faso had the lowest QCIs, at 78.5, 77.1, and 75.2, respectively. QCI showed a positive correlation with a country's level of economic development, with lower quality of care observed in those under 10 and over 95 years, and largely equal quality of care received between genders. Conclusions This study revealed differences in the quality of care for NTDs and malaria across regions, genders, and age groups. There is an urgent need to improve care quality, particularly in low SDI areas and among young children. The study provides recommendations for enhancing the quality of care for NTDs and malaria and for developing more effective public health interventions.